STRATEGI MANAJEMEN STRES KERJA PADA KARYAWAN TOKO RITEL (STUDI KASUS KARYAWAN ALFAMART SOEKARNO HATTA PROBOLINGGO) - Handayani, Nindyah Siska; Kholisah, Nur; Putri Dwita, Riska Dita; Adawiyah, Rofiatul; Haris, Syaiful; Sulaiman, Sulaiman; Kulsum, Ummi; Kartikawati, Yeni (HUMAN FALAH: Jurnal Ekonomi dan Bisnis Islam, 2025)
This study aims to examine in depth the work stress management strategies applied by employees and companies at Alfamart Soekarno Hatta, Probolinggo City. The approach used is qualitative with the type of case study, data obtained through interviews and documentation of five informants consisting of COS, ACOS, and Crew. The results of the study show that work stress management strategies are carried out through two approaches, namely individuals and companies. In the individual approach, employees manage stress by getting enough rest, engaging in enjoyable activities such as shopping, fishing and traveling, and sharing stories or confiding with colleagues as a form of social support. Meanwhile, the company's approach plays a role through gatherings, briefings and bonuses as a form of employee appreciation and relaxation. The application has been proven to be able to reduce stress levels, increase motivation and create a productive work environment. Companies are advised to strengthen stress management programs through more flexible work schedule arrangements in SO Grand activities, non-material appreciation, and regular stress management training.